A Relação formação profissional / Mercado de Trabalho: percepção dos assistentes sociais não-inseridos no mercado de trabalho do Serviço Social em Natal/RN - Cordeiro, Ana Paula de Moura (2005)
The study is about the non-insertion of the Social Assistant in the work market of Natal/RN, emphasizing the perception those Social Assistants have about this problem. We try to analyze the relation that those workers figure out about their non-insertion in the work market and their professional formation. The problem is related to the present unemployment rates in our society, which results of the changes that have affected the world of work as a whole in the wake of the Productive Restructuring and State Reformation supported by the neo-liberalism ideological system. We realize that these factors have deeply affected the configurations of the work market in general; especially those related to professions whose challenges multiply obstacles not only to the insertion of new workers, but to their staying in their job. We note that the reality of the work market has been built up on the decrease of the work force opportunities and the increase of the selectivity criteria to insertion of new workers. In consequence, unemployment rates increase everywhere, regardless of place, profession or education level of the workers. Work and management changes have brought about new challenges to professional formation. The presence of neo-liberalism productive and market logic demands a more adequate professional formation to work market from their candidates to a job. Due to the numberless difficulties workers face nowadays to enter the world of work, society itself and workers in general begin to question the profession of their choice, the kind of formation they have got, and frequently they lay the blame of their professional difficulties on it. This result has come out from the research we did with some social assistants not inserted in the professional work market in Natal/RN. The research reveals too that those unemployed professionals see their difficulties connected to their professional formation and they happen to say that the main challenge they face today is to get acknowledgment to the significance and importance of their profession